Attitude and Vaccination Status of Healthcare Workers against Hepatitis B Infection in a Teaching Hospital, Ethiopia. (2nd April 2018) - Akibu, Mohammed; Nurgi, Sodere; Tadese, Mesfin; Tsega, Wendwesen Dibekulu
Abstract : Background . World Health Organization and Centers for Disease Control and Prevention recommend all health professionals to get vaccinated against hepatitis B virus before they start the clinical attachments during their stay in the medical school. However, only 18–39% of healthcare workers in low- and middle-income countries received the vaccine. Therefore, this study aims to determine the attitude and vaccination status of health professionals working at Adama General Hospital and Medical College. Methods . An institution-based cross-sectional study was conducted from December 2016 to February 2017 with 403 health professionals working at Adama General Hospital and Medical College. Data were collected using self-administered questionnaire distributed at the participant's work unit and analyzed using SPSS version 20. Multiple logistic regression analysis was conducted to identify factors that affect the complete vaccination status andp value < 0.05 was considered statistically significant. Result . The prevalence of complete vaccination against hepatitis B virus was 25.6%. The most frequently mentioned reasons for not being vaccinated were high cost of the vaccine (41%) and unavailability of the vaccine (36%). More than three-fourths (77.8%) of study participants strongly agreed that hepatitis B is a major public health threat and there was tendency among participants to believe that their profession will put them at increased risk of acquiring the disease (strongly agreed: 75.9%). Attending infection-prevention training [AOR = 2.3; 95% CI, 1.24–6.31], history of exposure to risky behavior [AOR = 5.5; 95% CI, 2.86–9.29], and long years of work experience [AOR = 3.1; 95% CI, 1.98–5.24] were statistically significant with complete vaccination status. Conclusion . Only one-quarter of health professionals received the recommended full dose of the vaccine. Sustained hepatitis B vaccination programs for healthcare workers need to be established by collaboration of different stakeholders to optimize health professionals' safety against this contagious infection.